Detection of Human Papilloma Viruses type 16 and type 18 in patients with transitional cell carcinoma of the bladder by in situ hybridization - Hussein, Areej A.; Karhoof, Jasim M.; Hussein, Alaa G. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Transitional cell carcinomas (TCC) of the bladder are a major health problem. Recently, some studies link high risk Human papilloma viruses’ type 16 and type 18 with bladder carcinoma. Materials and methods: Fifty formalin fixed, paraffin embedded tissues with TCC of the bladder from Specialized Surgical Hospital in Baghdad were included in this study. In addition, ten apparently normal bladder autopsies were collected from the Forensic Medicine Institute Archives and used as control group. Tissue blocks were sectioned and sticked on charged slides and used for the detection of HPV-16 and HPV-18. Results: The expression of HPV-16 and HPV-18 DNA signals in TCC of the bladder tissues in the present study was 36% (18 out of 50) and 14% (7 out of 50) respectively, where strong correlation was found between expression of HPV-16 and TCC of the bladder while no correlation with HPV- 18. Conclusion: HPV-16 and HPV-18 might have an important role in the course of TCC of the bladder.